Factors sustaining legitimacy of smoking in Vocational Education and Training (VET) schools: a qualitative needs assessment - Dina Danielsen; Johan Lerbech Vinther; Ditte Heering Holt; Gitte Sofie Jakobsen; Lotus Sofie Bast; Susan Andersen (BMC, 2024)
Abstract Background Most adult smokers started smoking in their teenage years, which increases the risk of nicotine dependence. In Denmark, there is a high prevalence of youth smoking among students in Vocational Education and Training (VET). However, reducing and preventing smoking in this group is a major challenge. This article presents a needs assessment aimed to explore factors sustaining legitimacy of smoking in VET schools and consider the measures needed to prepare VET schools' implementation of smoking reduction and prevention interventions. Methods Participant observations were conducted in four VET classes representing three VET schools in Denmark with a duration of four days each. Individual, semi-structured interviews were conducted with teachers, managers, and a student advisor, as well as four focus groups with a total of 20 students. Interviews were audio-taped, transcribed, and the data material was analyzed following Malterud's systematic text condensation. Findings Factors that helped sustain legitimacy of smoking in VET schools included a positive and normalized attitude towards smoking at home and among friends, an understanding of smoking as an integral and expected practice in VET professions and schools, a perceived reliance on smoking as an icebreaker in new social relations and as a pedagogical tool, and smoking as a habit and a means to deal with boredom and stress relief. Conclusions The factors sustaining legitimacy of smoking in VET schools are reciprocal and call for smoking reduction and prevention intervention efforts which consider and address social influence, habitual behavior, and psychological needs, as well as changes at the policy level.